Networks that Transform: Mapping the National Interethnic Women's Network for Environmental Defense | A Participatory Exercise - Howland, Fanny Cecile; Gonzalez Rodriguez, Carlos Eduardo; Quintero, Diana Katherine; Casanova, Alexander Buritica; Salas, Daniela; Urbano, Angélica (CGIAR System Organization, 2024)
On July 3rd, 4th, and 5th, 2024, the “Training Workshop on Social Network Analysis and Its Application in Territories’ was held at the Alliance of Bioversity and CIAT campus in Palmira, Colombia. This event was conducted within the framework of the CGIAR initiative on National Policies and Strategies and with the support of the CGIAR Gender Platform aligned with the Alliance of Bioversity and CIAT, the Natura Foundation and the Rural Women’s Directorate of the Ministry of Agriculture and Rural Development (MADR) in an activity that combined training on social network analysis with its application to the National Interethnic Women’s Network for the Environment Defense. Through this exercise, the role of this network in policy influence territorial issues related to gender and environmental matters was successfully mapped, designed, and understood.